Language anxiety in ESP classrooms: a Malaysian context / Suhaily Abdullah - Abdullah, Suhaily (2008)
The aim of this study is to determine the difference in language anxiety level between certificate and diploma students in learning English at the tertiary level (polytechnics setting) and also to investigate the relationship between students’ language anxiety and their language performance. Participants of the study included 134 second-semester-commercial students of Politeknik Kota Bharu in Kelantan who were learning English in ESP context. A revised version of standardized anxiety scale, namely Foreign Language Classroom Anxiety Scale (FLCAS) of Horwitz et al. (1986), and a set of A2004 standardized quiz were used to investigate the relationship between language anxiety and students’ performance. Findings suggested that certificate students were found to have significantly higher anxiety level as compared to diploma students and language anxiety was negatively significantly correlated with the result of second standardized quiz. Based on these findings, some pedagogical implications for reducing students’ language anxiety were proposed for teachers and some recommendations for future research were included.